A model of the basic components in the seismic Vrancea zone - R.Z. Burtiyev; V.Yu. Kardanets (Геофизический журнал, 2020)
Seismic processes occur and develop temporally and spatially under the action of internal determinism of global tectonics. Uncertainties related to interlacement of internal physical fields of the Earth and gravity forces of celestial bodies and their effect on global tectonics introduce an element of randomness to models of seismicity. Seismic processes are complicated and multiform because their formation is conditioned by complex variegated geological-geophysical processes occurred in the interior of the Earth and characterized by a set of manifold parameters and the results of their observations are presented as multivariate accidental values. While studying such multivariate processes the question arises: if we can set aside a part of parameters or substitute them by minor number of some of their functions and preserve at the same time all the information? For solving this problem there is a factor analysis based on finding minimal number of factors forming the maximum share of data dispersion. In the studies of the complicated nature of seismicity the factor analysis forwards a deeper understanding of the essence of seismic processes because interrelation of seismic parameters must be conditioned by parameter relations which revealing is a task of factor analysis. The modern models of seismicity and the theories explaining appearance of the earthquakes are based on indirect data, mainly on seismic observations. The basic mission of geophysical studies is solving of inverse problem, i. e. determination of the structure of the medium according to observations of physical fields characteristics. Special features of seismic actions of each earthquake is determined by such of its characteristics as tectonics, the depth of a focus, mechanism, geometry of the focus, direction and the running of the process of rocks rupture and other parameters. The pattern of a microseismic field is a reflection of all these factors effect and of local geological features on manifestations of seismic effect in the sites of day surface.